(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Direct current (DC) motors are widely used because of their easily controllable and reliable access. DC motors have many salient features that includes a wide range of torque speed control, reliable operation with greater efficiency and a greater starting torque and many more. A nonlinear model for a DC motor can be represented for considering all uncertainties and non linearities. In this paper, DC motor is studied which is having a second order system. Many controllers are being used for controlling speed of DC motor. An analysis is carried out on mathematical model of DC motor whose field is excited by an external or separate supply. Tuning of FOPID parameters using Ant Colony Optimization Technique (ACO) is discussed here.